Feasibility Analysis of Thermal Oxidizer to Determine Remaining Life Using Fitness- for-Service Level 3 Method - Yudistirawan, Yudhi; Dhaneswara, Donanta; Putra, Wahyuaji Narottama; Widyaputra, Gama; Suci, Dewi Kurnia; Mahardhika, Agung Putra (Journal of Materials Exploration and Findings, 2026)
An aged thermal oxidizer (TOX) in the oil and gas industry necessitates a comprehensive evaluation to ensure its continued safe operation. This study presents a Remaining Life Assessment (RLA) and a Fitness for Service (FFS) evaluation for the four main components of the TOX, in accordance with API 510, API 579/ASME FFS-1, and ASME BPVC Section VIII Div-1 standards. The investigation includes the determination of maximum stress and maximum temperature required to assess the operational viability of the reactor. The four components are radiant, convection, transition, and stack sections—were modeled using the finite element method (FEM). Following the geometric modeling, an FFS evaluation was conducted based on two criteria: stress and temperature, to ascertain whether the TOX remains safe and operational until the end of its service life. Based on the FFS assessment, the TOX structure has been deemed fit to operate and acceptable for use throughout its remaining service life. Subsequently, a remaining life assessment performed on these components indicated an estimated service life of 20 years. According to the analyses carried out, the maximum stress observed is 160 MPa in the radiant section, while the highest temperature, recorded at 392 °C, occurs in the convection and transition sections. These results indicate that the radiant area particularly the upper radiant component, poses the highest risk due to the stress concentrations at its peak levels. In conclusion, although the TOX system is currently operating safely, periodic inspections are essential to ensure its continued secure operation until the end of its remaining service life.